From Blair to Brown: All change? New leadership, new priorities, new policies - Stephanie Claudia Hofmann; Roderick Parkes (Stiftung Wissenschaft und Politik (SWP), 2007)
Analyses of the likely changes to British foreign and European policies that a government under Gordon Brown will herald have been highly speculative: Although Brown's style of government is well-documented, the substance of his plans in this area remains somewhat shrouded in mystery. Today, the defining characteristic of Brown's agenda in this area prioritises tackling 'global problems', such as poverty, over European policy and modes of international action. Yet, given the growing constraints on the exercise of prime-ministerial power in Britain, this air of mystery appears increasingly unimportant: The greatest source of continuity and change in policy may not be Brown but rather the resurgent domestic actors which have increased their clout in the dying days of the last Blair government and whose preferences are well-documented. Brown's capacity to realise his priorities depends in no little part upon his capacity to change his style of government and outmanoeuvre these resurgent actors. (SWP Comments / SWP)
Keywords: 320